2007
DOI: 10.1038/sj.bmt.1705703
|View full text |Cite
|
Sign up to set email alerts
|

The presence of functional CCR5 and EBV reactivation after allogeneic haematopoietic stem cell transplantation

Abstract: EBV reactivation is a serious complication affecting the recipients of allogeneic haematopoietic stem cell transplants (allogeneic HSCT). Recent reports have suggested that EBV reactivation induces increased expression of C-C chemokine receptor-5 (CCR5) or its ligands. Therefore, the 32-nucleotide deletion within the CCR5-encoding gene (CCR5D32 polymorphism) was analysed in 92 recipients of allogeneic HSCT and their donors and related with EBV load. In addition in 30 patients, at the same time points employing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 18 publications
(18 reference statements)
2
30
0
1
Order By: Relevance
“…Thus, CCL3 and CCL4 serve as survival and growth factors in B cells. In addition, patients carrying high copy numbers of EBV have significantly higher levels of CCR5, a binding receptor of CCL3 and CCL4 (24). In our study, we found that CCR5 is highly expressed during primary infection and constitutive expression is maintained in EBV-immortalized LCLs (data not shown).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Thus, CCL3 and CCL4 serve as survival and growth factors in B cells. In addition, patients carrying high copy numbers of EBV have significantly higher levels of CCR5, a binding receptor of CCL3 and CCL4 (24). In our study, we found that CCR5 is highly expressed during primary infection and constitutive expression is maintained in EBV-immortalized LCLs (data not shown).…”
Section: Discussionsupporting
confidence: 48%
“…In our study, we found that CCR5 is highly expressed during primary infection and constitutive expression is maintained in EBV-immortalized LCLs (data not shown). On the other hand, patients with a CCR5 gene deletion have a nonfunctional CCR5 chemokine receptor, leading to a low EBV load in sera after transplantation (24).…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Supporting the role of CCR5 in GVHD, a single nucleotide polymorphism (SNP) in chemokine ligand 5 (CCL5, also known as RANTES) has been significantly associated with a greater incidence of chronic graft-versus-host disease (cGVHD). 12 The authors of another study 13 demonstrated that recipients with the nonfunctional CCR5⌬32 allele were less likely to develop acute graft-versushost disease (aGVHD), and other authors [14][15][16] have found CCR5 promoter polymorphisms to be predictive of the response to chemotherapy in leukemia and in the likelihood of cytomegalovirus and Epstein-Barr virus reactivation after HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] In particular, blockade or lack of the chemokine receptors CCR2 and CCR5 on donor leukocytes by administration of anti-CCR5 antibody or infusion of CCR2 Ϫ/Ϫ T cells reduces the incidence of GVHD in animal models. 10,11 Supporting the role of CCR5 in GVHD, a single nucleotide polymorphism (SNP) in chemokine ligand 5 (CCL5, also known as RANTES) has been significantly associated with a greater incidence of chronic graft-versus-host disease (cGVHD).…”
Section: Introductionmentioning
confidence: 99%
“…Cytomegalovirus (CMV), Human Herpes Virus-6 (HHV-6), and Epstein-Barr Virus (EBV) reactivations were monitored in patients after transplantation using quantitative PCR as previously described [7][8][9][10]. In brief, DNA was extracted from peripheral blood (QiAmp Blood Kit; Qiagen, Hilden, Germany) according to the manufacturer's instructions.…”
Section: Monitoring Of Viral Reactivationsmentioning
confidence: 99%